2021
DOI: 10.3390/su13168819
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Structural and Energy Improvement in Mid-Rise Unreinforced Masonry Apartment Buildings. A Case Study in Mestre (Northeast Italy)

Abstract: Two-thirds of the Italian building stock was already built by the 1970s, largely according to gravity load design and using economical materials and poor workmanship. Currently, the structures, fixtures, and fittings of these buildings have reached the end of their service life, and they require both an assessment and an update to meet new standards and new needs. As an example of a common type, this article deals with the assessment of the present state and the proposal of an integrated structural and archite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…Another pilot study was conducted on assessing energy use and overheating risk in net-zero-energy residential buildings under the Horizon 2030 research project with case studies in Cyprus, France, Italy, and the UK. Design, optimisation, implementation and monitoring of advanced energy efficiency solutions to upgrade the building envelope of the inefficient residential building stock were assessed [73][74][75][76].…”
Section: Thermal Comfort In Residential Buildings In Europementioning
confidence: 99%
“…Another pilot study was conducted on assessing energy use and overheating risk in net-zero-energy residential buildings under the Horizon 2030 research project with case studies in Cyprus, France, Italy, and the UK. Design, optimisation, implementation and monitoring of advanced energy efficiency solutions to upgrade the building envelope of the inefficient residential building stock were assessed [73][74][75][76].…”
Section: Thermal Comfort In Residential Buildings In Europementioning
confidence: 99%
“…Electricity, hard coal, at power plant/ES 4 Electricity, natural gas, at power plant/ES 4 Electricity, PV, at 3 kWp flat roof installation, multi-Si/CH 3 Notes: 1 Cement was modified to present Portland cement with 95% clinker (CEM I) and Portland cement with 65% clinker (CEM II) used in Israel. 2 Electricity was modified to present Israeli electricity sources: 31% coal, 56% natural gas, and 13% PV, used in 2020, and 8% coal, 57% natural gas, and 35% PV, planned for 2025. 3 Switzerland.…”
Section: Lca Of P and Oe Stagesmentioning
confidence: 99%
“…This large amount of energy consumption can be significantly reduced with proper insulation of the building's envelope. For example, Sbrogiò et al [2] and Al-Saqqaf et al [3] used typical energy-saving technologies (e.g., cladding all exterior walls with mineral wool, insulating panels for floor slabs, double walls with polystyrene insulation, installation of a green roof and double low-E glass) to reduce energy consumption in heating and cooling old or heritage buildings. In both cases, the authors reported a significant energy-saving effect for the operational energy (OE) stage.…”
Section: Introductionmentioning
confidence: 99%
“…The retrofit techniques analysed herein are designed to improve the seismic and energetic behaviour of existing masonry buildings, with the aim of guaranteeing the safety of the occupants while preserving the building heritage thanks to integrated and fast-execution interventions. Structural, energetic, and architectural aspects must be considered simultaneously to obtain a cost-optimal renovation [3,4]. In this respect, the use of timber elements appears as promising.…”
Section: Introductionmentioning
confidence: 99%